Fantasy cinema : impossible worlds on screen - Butler, David (London ; New York : Wallflower, 2009)
"Often dismissed as simple tales of sword and sorcery, fantasy is one of the fundamental impulses in filmmaking, a source of some of the most vivid and memorable films ever made that reaches far beyond the confines of a single genre. As well as some of the major genres, stylistic approaches and exponents of cinematic fantasy, from Georges Melies, Walt Disney, and Andrei Tarkovsky to contemporary fantasists such as Terry Gilliam and Peter Jackson. This volume focuses on fantasy's social function with case studies including The Thief of Baghdad (1924), Excalibur (1981), the Lord of the Rings trilogy (2001-03), and Bruce Almighty (2003). and interpretations. Taking in the popular and the experimental, subversive desires and reactionary dreams, this book is an engaging introduction to one of the vital energies in cinema." -- Book cover.
Introduction : the problem of fantasy -- Establishing fantasy : definitions and developments -- Types of fantasy : angels, genies, swords, and sorcerers -- Realising fantasy : audio-visual style -- Interpreting fantasy : functions and beliefs.
Filmografija: str. 125-130.
Bibliografija: str. 131-142. - Kazalo
Keywords: Fantasy films -- History and criticism; fantastični film